An enhanced context-aware face recognition alert system for people with hearing impairment - Abbas, M.K. (Springer Verlag, 2019)
The life of deaf people or People with Hearing Impairments (PHIs) is difficult as they have to face challenges in identifying sounds like a visitor pressing the doorbell. The traditional doorbell uses an audio signal to notify people. However, it does not notify PHIs because PHIs are insensitive to sound. Due to the lack of help from support services, PHIs may not have normal daily lives. Therefore, it is necessary to propose an efficient doorbell solution in helping PHIs to be notified, and the intangible benefit for PHIs is that it will reduce their dependency on their families in their daily lives. This paper proposes a hybrid (Image Processing and Context-Aware Computing) alert system that would notify PHIs by using visual communication signals and tactile cues instead of audio signals. Compared with the existing solutions, the enhanced face recognition feature included in the proposed system design, made it smart enough to know when the visitorâs image has to be snapped or not and how to reduce the transmission time of the image. In addition, what is context aware, and how the context aware feature will benefit the system design is also discussed. On the other hand, the intangible benefit of this research would be helping PHIs by reducing their dependency on others and building their self-confidence. Â© Springer Nature Switzerland AG 2019.